Preparation method of expanded graphite-based composite material based on molten salt intercalation and controllable deintercalation thereof

By using the method based on molten salt intercalation and its controllable detachment, the problems of difficult to regulate the expansion effect, high energy consumption and high safety risks in the existing expanded graphite preparation methods are solved, and the preparation of expanded graphite-based composite materials with low cost, low energy consumption and high stability are realized.

CN119841312AActive Publication Date: 2025-04-18GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510330703.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The existing methods for preparing expanded graphite have problems such as difficult to regulate the expansion effect, excessive volume changes, high energy consumption and high safety risks.

Method used

Using a method based on molten salt intercalation and its controllable detachment, the expanded graphite matrix composite material is prepared by mixing the graphite substrate with the intercalation agent, reacting the molten salt intercalation and secondary heating, so as to sublimate and remove the intercalation agent to prepare an expanded graphite-based composite material.

Benefits of technology

The preparation of various different expansion effects of expanded graphite is achieved, which reduces energy consumption and cost, improves product stability and safety, and efficient recycling of intercalators reduces preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841312A_ABST
    Figure CN119841312A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an expanded graphite-based composite material based on molten salt intercalation and controllable deintercalation thereof, and belongs to the technical field of preparation of modified expanded graphite. The preparation method of the expanded graphite-based composite material comprises the following steps: mixing a graphite base material with an intercalator, and carrying out a molten salt intercalation reaction under a closed condition to obtain a graphite intercalation compound; and under a semi-closed condition, carrying out secondary heating on the graphite intercalation compound, so that the intercalation agent is sublimated and removed to obtain the expanded graphite-based composite material based on molten salt intercalation and controllable removal thereof. The intercalator is a metal salt capable of sublimating under a secondary heating condition. According to the method disclosed by the invention, the intercalator is completely or partially separated from the graphite intercalation compound at a relatively low secondary treatment temperature, so that graphite with different expansion effects is obtained, the residual rate of the intercalator is 0-100%, and the technical problems of single product type, production safety and low cost existing in preparation of expanded graphite by a strong oxidation method in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of modified expanded graphite, and more specifically relates to a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof. Background Art

[0002] Expanded graphite has a wide range of applications. Its synthesis method generally uses graphite as a matrix, and uses strong oxidants such as concentrated sulfuric acid, fuming nitric acid and potassium permanganate to perform edge oxidation and internal intercalation under ice bath conditions. After separation and purification, graphite oxide is obtained. Then, the graphite oxide is heated at a high temperature of more than 900°C or by microwaves to decompose sulfate ions into sulfur dioxide, and edge hydroxyl groups, epoxy groups and carboxylic acids decompose into carbon dioxide. The graphite layer is opened by the force generated by expansion. The expanded graphite obtained by the traditional strong oxidation method has a very high expansion degree and has been produced on a large scale. However, it also has several disadvantages: (1) It is not easy to control different expansion effects; (2) The volume will gradually collapse during storage, and it must be expanded and used immediately, otherwise key indicators such as porosity will fluctuate too much and cannot be calibrated; (3) High energy consumption; (4) High process safety risk. In order to make up for the defect of too few types of different expansion effects, researchers have developed a variety of expanded graphite with different synthesis routes, such as the autoclave method using the supercritical effect of CO2. The autoclave method has increased safety risks. Although it has certain value, it is currently difficult to mass produce. In order to avoid excessive volume changes, most of the currently available expanded graphite is in the form of expandable graphite (graphite oxide). Although the problem has been solved, it is extremely inconvenient. In order to reduce energy consumption and safety risks, researchers have introduced a weak acid electrolyte method, such as using ammonium persulfate and dilute sulfuric acid to slowly oxidize graphite. The expanded graphite prepared by the weak acid electrolyte method has a low expansion rate and low efficiency, and cannot be widely promoted.

[0003] In view of the many problems existing in the above-mentioned preparation methods of expanded graphite, it is of great significance to study a preparation method of expanded graphite that can obtain a variety of different expansion effects, has low cost, low energy consumption, and high stability. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, so as to solve the problems existing in the above-mentioned prior art and realize the preparation of expanded graphite with low cost, low energy consumption and high stability, which can obtain a variety of different expansion effects.

[0005] To achieve the above object, the present invention provides the following solutions: One of the technical solutions of the present invention is to provide a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, comprising the following steps: The graphite substrate is mixed with the intercalation agent, and a molten salt intercalation reaction is carried out under closed conditions to obtain a graphite intercalation compound; Under semi-closed conditions, the graphite intercalation compound is heated for a second time to allow the intercalation agent to sublime and escape to obtain the expanded graphite-based composite material based on molten salt intercalation and controllable escape; The intercalant is a metal salt that can sublime under secondary temperature rising conditions.

[0006] Preferably, the graphite substrate includes one or more of natural graphite, artificial graphite, microcrystalline graphite, expanded graphite and multilayer graphene; the intercalant includes one or more of metal halides, metal sulfides and metal oxides, the metal halide includes one or more of aluminum chloride, molybdenum chloride, niobium chloride, titanium chloride and gallium chloride, the metal sulfide includes mercuric sulfide, and the metal oxide includes mercuric oxide.

[0007] Preferably, the mass ratio of the graphite substrate to the intercalant is 1:0.1-14.

[0008] Preferably, the temperature of the molten salt intercalation reaction is 100-800°C, the time is 0-24h, and is not 0.

[0009] Preferably, the secondary heating temperature is 100-800°C, the heating rate is 10°C / min, the time is 0-1h, and is not 0.

[0010] Preferably, the molten salt intercalation reaction also includes a step of controlling the order of the obtained graphite intercalation compound by using chlorine partial pressure; the reagent providing the chlorine partial pressure includes one or more of liquefied chlorine, chlorosuccinimide, phosphorus trichloride, phosphorus pentachloride, thionyl chloride and sulfonyl chloride. By controlling the amount of such reagents, different chlorine partial pressure values ​​can be provided. On the premise of ensuring sufficient intercalation agent, the greater the amount, the greater the pressure, and the more perfect the product order. Excessive high pressure is not conducive to safety protection. The chlorine partial pressure of the present invention is 5~8MPa.

[0011] Furthermore, it is necessary to ensure that the reagent providing the chlorine partial pressure does not mix with or contact the reactants.

[0012] Furthermore, the molten salt intercalation reaction and the secondary heating are both carried out in a reactor, specifically: a graphite substrate is mixed with an intercalation agent, and placed in a closed reactor for a molten salt intercalation reaction to obtain a graphite intercalation compound; then the reactor is adjusted to a semi-closed state, and placed in a sealed recovery bottle for a secondary heating to obtain the expanded graphite-based composite material based on molten salt intercalation and its controllable release.

[0013] After the secondary temperature-raising reaction of the present invention is completed, the intercalation agent is sublimated into a recovery bottle, and the product remains in the reaction kettle. By recovering the substances produced in the recovery bottle, the intercalation agent can be efficiently recovered, thereby reducing the preparation cost.

[0014] In addition, during the secondary heating process, the intercalant is relatively active and sublimates under semi-sealed conditions accompanied by a small amount of oxidation. The presence of these oxides is beneficial to the room temperature stability and performance of the graphite intercalation compound containing the intercalant.

[0015] Preferably, the second heating further includes the steps of removing impurities and drying the product.

[0016] Preferably, the method further comprises the step of modifying the expanded graphite composite material based on molten salt intercalation and controllable release thereof.

[0017] The second technical solution of the present invention: provides an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof prepared by the preparation method of the expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, wherein the intercalation agent residual rate of the expanded graphite-based composite material based on molten salt intercalation and controllable release thereof is 0~100%, and is not 0.

[0018] The third technical solution of the present invention is to provide the application of the expanded graphite-based composite material based on molten salt intercalation and controllable release thereof in battery preparation.

[0019] The technical principle of the present invention is: The present invention provides a method for preparing an expanded graphite-based composite material with low cost, controllable expansion degree, safety and high efficiency, so as to solve the technical problems in the types, stability, production safety and cost of products with different expansion effects existing in the expanded graphite prepared by the prior art.

[0020] The present invention uses a low-boiling-point intercalant to prepare an intermediate product (graphite intercalation compound). The low-boiling-point intercalant can generate expansion thrust like an acid radical ion under instantaneous high temperature conditions, thereby preparing expanded graphite. This method has the following advantages: (1) Different amounts of intercalant embedded can produce different expansion effects. By preparing pre-intercalated graphite with different intercalation orders, expanded graphite with different expansion effects can be prepared in a controllable manner; (2) The preparation temperature and post-treatment sublimation temperature of the graphite intercalation compound corresponding to the low-boiling-point compound are relatively low, with low energy consumption and low cost; (3) After a large amount of intercalant is removed, the expanded graphite still carries a small amount of residual intercalant, which can make the expanded graphite structure relatively stable and maintain it for a longer time at room temperature; (4) The entire process does not involve strong acid reactants and ultra-high pressure process conditions, and has a high safety factor; (5) Through effective process design, most of the removed intercalant can be recovered, further reducing costs.

[0021] The present invention adopts a specific type of intercalation agent, controls the temperature and duration of the secondary heating, and adjusts the residual rate of the intercalation agent to obtain expanded graphite-based composite materials with different residual rates (different expansion effects). The expanded graphite-based composite material can be used after impurities are removed, or can be used directly in the form of a composite material without impurities being removed.

[0022] Compared with the existing expanded graphite preparation process which requires a high expansion temperature (800-1000°C), the present invention uses a specific type of intercalation agent to prepare graphite intercalation compounds of different orders, and can achieve the preparation of expanded graphite with controllable expansion effect at a lower secondary heating temperature (100-800°C). Compared with the existing technology, the present invention reduces energy consumption and ensures a lower preparation cost.

[0023] When the expanded graphite is prepared by the preparation method of the present invention, a small amount of residual intercalating agent and oxides oxidized during the sublimation of the intercalating agent are still present in the expanded graphite after a large amount of intercalating agent is removed, so that the structure of the expanded graphite can be relatively stable and can be maintained for a longer time at room temperature, and the product stability is higher.

[0024] The present invention discloses the following technical effects: 1. The present invention adopts graphite intercalation compounds as intermediate products, uses a relatively low secondary treatment temperature to completely or partially remove the intercalation agent from the graphite intercalation compounds, and obtains fully expanded and slightly expanded graphite, with an intercalation agent residual rate of 0-100%, thereby solving the technical problems of product stability, production safety, and cost in the prior art of preparing expanded graphite by a strong oxidation method.

[0025] 2. The present invention can controllably prepare expanded graphite with different expansion effects, thereby solving the problem that the existing method for preparing expanded graphite cannot control the expansion effect to obtain expanded graphite with different expansion effects.

[0026] 3. The present invention has low energy consumption and low cost; the obtained product structure can be kept for a longer time at room temperature; the safety factor is high; the intercalation agent used can be recycled, which is environmentally friendly and sustainable; the synthesis method is simple to operate, with high production efficiency and high raw material utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a flow chart of the preparation method of the present invention and a structural diagram of the device required for the preparation process, wherein 1-quartz bottle, 2-flange type hydrothermal reaction kettle, 3-steel recovery bottle, 4-overflow gap after adjusting the air tightness, 5-intercalation agent condensed on the wall of the recovery bottle after overflow; Figure 2 The TG measurement results of the intercalation agent residues described in Example 1, Example 3, Example 4 and Comparative Example 1; Figure 3The scanning electron microscope images of the products obtained in Comparative Examples 1-2 and Examples 1-4; Figure 4 The XRD patterns of the intermediate products obtained in step S1 of comparative examples 1 to 2 and embodiments 1 to 4 and the final products obtained in step S3; Figure 5 The performance diagram of the battery prepared from the final product obtained in step S3 of comparative example 1, example 2 and example 4; Figure 6 This is the crystallization of the intercalation agent on the wall of the flange-type hydrothermal reactor during the preparation process of Example 3. DETAILED DESCRIPTION

[0028] The present invention provides a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof (the specific process is as follows Figure 1 ), including the following steps: The graphite substrate is mixed with the intercalation agent, and a molten salt intercalation reaction is carried out under closed conditions to obtain a graphite intercalation compound; Under semi-closed conditions, the graphite intercalation compound is heated for a second time to allow the intercalation agent to sublime and escape to obtain the expanded graphite-based composite material based on molten salt intercalation and controllable escape; The intercalant is a metal salt that can sublime under secondary temperature rising conditions.

[0029] The intercalation agent in the preparation method of the present invention is mainly a metal compound that is easy to insert into the graphite interlayer and easy to sublime. By using the intercalation and deintercalation, the expansion and expansion of graphite are achieved. It can be understood that the core reaction of the present invention is the embedding and deintercalation reaction of the intercalation agent in graphite.

[0030] In the present invention, the graphite intercalation compound is obtained by compounding an intercalation agent and a graphite substrate. The graphite substrate includes but is not limited to one or more of natural graphite, artificial graphite, microcrystalline graphite, expanded graphite and multilayer graphene; the intercalation agent includes but is not limited to one or more of metal halides, metal sulfides and metal oxides, the metal halides include one or more of aluminum chloride, molybdenum chloride, niobium chloride, titanium chloride and gallium chloride, the metal sulfides include mercuric sulfide, and the metal oxides include mercuric oxide.

[0031] In some embodiments, the graphite intercalation compound can be prepared by a direct mixing method, a molten salt method, and a dual chamber method.

[0032] In some embodiments, before mixing the graphite substrate with the intercalation agent, the graphite substrate is further dried; the drying temperature is 80° C., and the drying time is 4 hours.

[0033] The present invention does not impose any particular limitation on the particle size of the graphite substrate, as long as the product can be prepared.

[0034] The present invention does not impose any particular limitation on the mixing method of the graphite substrate and the intercalation agent, as long as uniform mixing can be ensured.

[0035] In the present invention, the mass ratio of the graphite substrate to the intercalant is preferably 1:0.1-14, more preferably 1:1-10, and more preferably 1:4.

[0036] In the present invention, the temperature of the molten salt intercalation reaction is preferably 100-800°C, more preferably 150-500°C, specifically 100°C, 150°C, 200°C, 250°C, 300°C, 400°C, 500°C; the time is preferably 0-24h, and not 0, more preferably 0.5min-23h, specifically 0.5min, 0.6min, 0.8min, 1min, 2min, 5min, 8min, 10min, 15min, 20min, 30min, 40min, 50min, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 15h, 18h, 19h, 20h, 22h, 23h or 24h.

[0037] In the present invention, the temperature of the secondary heating is preferably 100-800°C, more preferably 150-700°C, specifically 100°C, 150°C, 200°C, 250°C, 300°C, 400°C, 500°C, 600°C, 700°C or 800°C; the heating rate is preferably 10°C / min; the time is preferably 0-1h, and not 0, more preferably 0.25-50min, specifically 0.25min, 0.5min, 0.6min, 0.8min, 1min, 2min, 5min, 8min, 10min, 15min, 20min, 30min, 40min, 50min or 1h.

[0038] In some embodiments, the molten salt intercalation reaction further comprises a step of controlling the order of the resulting graphite intercalation compound by using a chlorine partial pressure. The chlorine partial pressure helps embedding the intercalation agent in the graphite. The reagent providing the chlorine partial pressure includes one or more of liquefied chlorine, chlorosuccinimide, phosphorus trichloride, phosphorus pentachloride, thionyl chloride and sulfonyl chloride.

[0039] In the present invention, it is necessary to ensure that the reagent providing the chlorine partial pressure does not mix with or contact the reactants.

[0040] The dosage of intercalating agent, temperature, pressure and defect distribution all have a certain influence on the order of the product. The influence of chlorine partial pressure is an efficient control method that combines the influence of pressure with the multiple influences of chlorine atom doping and vacancy effect. It is a method to control the order of the product by reducing the reaction energy barrier.

[0041] In the present invention, the molten salt intercalation reaction and the secondary heating are both carried out in a reactor, specifically: a graphite substrate is mixed with an intercalation agent, and placed in a closed reactor for a molten salt intercalation reaction to obtain a graphite intercalation compound; then the reactor is adjusted to a semi-closed state, and placed in a sealed recovery bottle for secondary heating to obtain the expanded graphite and expanded graphite-based composite material based on molten salt intercalation and controllable release thereof.

[0042] In the present invention, the reactor includes but is not limited to a general hydrothermal reactor, a step hydrothermal reactor, a flange hydrothermal reactor or a large customized hydrothermal reactor; the material of the recovery bottle includes but is not limited to steel, ceramic or glass.

[0043] In some embodiments, if batch production is considered, the intercalation agent embedding and extraction reactions can also be completed in an inert atmosphere; the inert atmosphere includes but is not limited to an argon atmosphere. In addition, a gas injection and pressure control device need to be designed separately to implement the inert atmosphere.

[0044] After the secondary temperature-raising reaction of the present invention is completed, the intercalation agent is sublimated into a recovery bottle, and the product remains in the reaction kettle. By recovering the substances produced in the recovery bottle, the intercalation agent can be efficiently recovered, thereby reducing the preparation cost.

[0045] In some embodiments, a simple intercalant recovery device can be designed to recover the intercalant using the specific heat capacity of the equipment and the furnace cooling sequence.

[0046] In another embodiment, if large-scale production is considered, a vacuum device at high temperature can be designed to recover the intercalation agent.

[0047] In some embodiments, the second heating further includes the steps of removing impurities and drying the product.

[0048] The graphite intercalation compound containing the intercalation agent itself has certain functionality, and the product that partially retains the intercalation agent can be directly used. In addition, the intercalation agent is relatively active, and sublimation under semi-sealed conditions is accompanied by a small amount of oxidation. The presence of these oxides is beneficial to the room temperature stability and performance of the graphite intercalation compound containing the intercalation agent, and can also be retained. Therefore, the above-mentioned cleaning, impurity removal and drying steps can be determined according to application needs.

[0049] In addition, the expanded graphite obtained after the release reaction usually contains impurities, such as intercalants and their oxides. The above impurities are likely to affect the physical and chemical properties of the expanded graphite, and are not conducive to the subsequent oxidation, sulfidation, phosphation, selenization and other treatments to enrich the types of expanded graphite. The presence of impurities can easily reduce the efficiency and effect of oxidation, sulfidation, phosphation, and selenization. Therefore, some application scenarios require the expansion of graphite to be impurity-free.

[0050] The present invention does not impose any particular limitation on the method of removing impurities.

[0051] In some embodiments, the product can be cleaned with a cleaning agent to achieve the purpose of removing impurities; the cleaning agent includes but is not limited to one or more of deionized water, organic solvents and acid-base reagents; the organic solvents include but are not limited to one or more of ethanol, methanol and acetone; the acid-base reagents include but are not limited to hydrochloric acid. The above cleaning agents can remove impurities and have little effect on expanded graphite with a low degree of expansion. However, it is not good for expanded graphite with a high degree of expansion. Therefore, for expanded graphite with a high degree of expansion, try not to clean it, or use a very simple cleaning process.

[0052] In another embodiment, the expanded graphite can be immersed in a cleaning agent and left to stand for a period of time until the impurities are removed. Alternatively, the expanded graphite can be immersed in a cleaning agent and mechanical cleaning can be used to accelerate the removal of impurities; the mechanical cleaning method includes but is not limited to ultrasonic cleaning or magnetic stirring cleaning.

[0053] The present invention does not impose any special restrictions on the time of impurity removal, as long as the impurities are completely removed. The pH value and color of the washing liquid can be used as the judgment criteria, and the impurity removal is considered to be completed when the washing liquid is close to neutral and the washing liquid is almost transparent.

[0054] In some embodiments, the time for removing impurities is 0 to 24 hours, and is not 0.

[0055] In some embodiments, the expanded graphite obtained after the impurities are removed can be dried, and can be placed in a vacuum drying condition at 60-80° C. for 10-15 hours.

[0056] Since the graphite intercalation compounds have a certain structural stability, the expanded graphite prepared through the above steps inevitably still contains trace amounts of metal compound intercalants. In order to enrich the types of expanded graphite, the expanded graphite-based composite materials can also be modified by substitution reaction to obtain metal compound-modified expanded graphite that is difficult to prepare directly.

[0057] In some embodiments, the method further includes the step of modifying the expanded graphite-based composite material based on molten salt intercalation and its controllable release; the modification treatment includes but is not limited to oxidation treatment, sulfurization treatment, phosphating treatment or selenization treatment.

[0058] The present invention does not impose any particular limitation on the specific steps of oxidation treatment, sulfidation treatment, phosphation treatment and selenization treatment, and the above treatments may be achieved by using commonly used technical means in the art.

[0059] When the expanded graphite prepared by the present invention is subjected to oxidation treatment, the intercalant (metal compound) can be oxidized to metal oxide, that is, expanded graphite modified with metal oxide can be obtained. In some embodiments, the oxidation treatment includes but is not limited to air oxidation, electromagnetic heating oxidation or microwave oxidation.

[0060] When the expanded graphite prepared by the present invention is subjected to a sulfurization treatment, the intercalation agent (metal compound) can be sulfurized into a metal sulfide, and thus expanded graphite modified with a metal sulfide can be obtained. In some embodiments, the sulfur source for the sulfurization treatment includes, but is not limited to, one or more of elemental sulfur, hydrogen sulfide, sulfur oxide, sodium sulfide, and thiourea; the sulfurization treatment includes, but is not limited to, elemental sulfur sulfurization, carbon disulfide sulfurization, or sulfur-containing organic sulfurization.

[0061] When the expanded graphite prepared by the present invention is subjected to phosphating treatment, the intercalating agent (metal compound) can be phosphated into metal phosphide, that is, expanded graphite modified with metal phosphide can be obtained. In some embodiments, the phosphorus source for the phosphating treatment includes but is not limited to one or more of elemental phosphorus, phosphine, phosphoric acid and sodium hypophosphite, and the phosphating treatment includes but is not limited to elemental phosphorus phosphating method or phosphorus-containing organic matter phosphating method.

[0062] The present invention has extremely high production efficiency. The present invention prepares expanded graphite with electrode material function, which can be expanded to the application fields of aviation phase change materials, military absorbing materials and the like. The ordinary expanded graphite preparation process requires the preparation of graphite oxide in liquid phase first, then cleaning and purification, and then high-temperature expansion to obtain expanded graphite, and then other composite methods are used to compound materials with specific functions into the expanded graphite. The present invention only requires a one-pot method, and this step can be achieved by heating twice. The product of the present invention can also be washed or not washed according to application needs. Compared with multiple steps, the one-pot method is more efficient.

[0063] The present invention has a very high raw material utilization rate. The present invention can make the sublimated raw materials reused repeatedly. It is found in the experiment that after deducting the intercalation residue (related to the application scenario), the recovery rate can reach up to 90%. If an industrial design is made, the recovery rate can be even higher.

[0064] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0065] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0066] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0067] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0068] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0069] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.

[0070] The original graphite PG used in the present invention is purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and other raw materials used are commercially available products unless otherwise specified. The sources of the commercially available products do not affect the technical effects of the present invention.

[0071] The room temperature involved in the present invention is 25±5°C unless otherwise specified.

[0072] Example 1 This embodiment provides a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, and the specific steps are as follows: Step S1: After drying 1 g of natural graphite with a particle size of 10 μm at 120° C. for 4 h, 4 g of anhydrous molybdenum chloride is quickly added and stirred at room temperature. After vacuum drying at 120° C. for 1 h, the mixture is transferred to a flange-type hydrothermal reactor, and 2 g of chlorosuccinimide (not mixed or contacted with the reactants) is additionally added to the gap of the flange-type hydrothermal reactor. The flange-type hydrothermal reactor is sealed and placed in a heating furnace, heated to 350° C. and kept warm for 24 h to obtain a graphite intercalation compound, i.e., an intermediate product of the first-order MoCl5-graphite intercalation compound is obtained.

[0073] Step S2: After the flanged hydrothermal reactor is completely cooled, the flange of the flanged hydrothermal reactor is loosened to facilitate gas overflow, and then placed in a sealable steel recovery bottle, and the recovery bottle is sealed. The whole is placed in a heating furnace and heated to 300°C (heating rate is 10°C / min) and kept warm for 1 hour. In this process, the intercalation product of the graphite intercalation compound obtained in step S1 is almost completely sublimated and released, causing graphite expansion.

[0074] Step S3: After the container is completely cooled, open the steel recovery bottle, scrape the anhydrous MoCl5 from the recovery bottle, collect, dry and seal. Open the flange hydrothermal reactor, scrape the expanded graphite from the inner tank, seal and collect. The final product is an expanded graphite-based composite material with a very low content of residual intercalation (content of 6%). Finally, 3.5g MoCl5 is recovered.

[0075] Example 2 This embodiment provides a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, and the specific steps are as follows: Step S1: After drying 1 g of natural graphite with a particle size of 10 μm at 120° C. for 4 h, 1 g of anhydrous molybdenum chloride is quickly added and stirred at room temperature. After vacuum drying at 120° C. for 1 h, the mixture is transferred to a flange-type hydrothermal reactor, and 1 g of chlorosuccinimide (not mixed or contacted with the reactants) is additionally added to the gap of the flange-type hydrothermal reactor. The flange-type hydrothermal reactor is sealed and placed in a heating furnace, heated to 350° C. and kept warm for 24 h to obtain a graphite intercalation compound, that is, an intermediate product of 3 to 7 order MoCl5-graphite intercalation compound is obtained.

[0076] Step S2: After the flanged hydrothermal reactor is completely cooled, the flange of the flanged hydrothermal reactor is loosened to facilitate gas overflow, and then placed in a sealable steel recovery bottle, and the recovery bottle is sealed. The whole is placed in a heating furnace and heated to 270°C (heating rate is 10°C / min) and kept warm for 5 minutes. During this process, the intercalation product of the graphite intercalation compound obtained in step S1 is partially sublimated and released, causing micro-expansion of graphite.

[0077] Step S3: After the container is completely cooled, open the steel recovery bottle, scrape the anhydrous MoCl5 from the recovery bottle, collect, dry and seal. Open the flange hydrothermal reactor, scrape the micro-expanded graphite from the inner tank, seal and collect. The final product is an expanded graphite-based composite material with a high content of residual intercalation (content of 50%). The obtained expanded graphite-based composite material is washed with deionized water, alcohol and acetone respectively and dried at 80°C for 12h. Finally, 0.8g MoCl5 is recovered.

[0078] Example 3 This embodiment provides a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, and the specific steps are as follows: Step S1: After drying 1 g of natural graphite with a particle size of 10 μm at 120° C. for 4 h, 9 g of anhydrous aluminum chloride is quickly added and stirred at room temperature. After vacuum drying at 120° C. for 1 h, the mixture is transferred to a flange-type hydrothermal reactor, and 2 g of chlorosuccinimide (not mixed or contacted with the reactants) is additionally added to the gap of the flange-type hydrothermal reactor. The flange-type hydrothermal reactor is sealed and placed in a heating furnace, heated to 200° C. and kept warm for 12 h to obtain a graphite intercalation compound, that is, an intermediate product of 1~2 order AlCl3-graphite intercalation compound is obtained.

[0079] Step S2: After the flanged hydrothermal reactor is completely cooled, the flange of the flanged hydrothermal reactor is loosened to facilitate gas overflow, and then placed in a sealable steel recovery bottle, and the recovery bottle is sealed. The whole is placed in a heating furnace and heated to 200°C (heating rate is 10°C / min) and kept warm for 1 hour. In this process, the intercalation product of the graphite intercalation compound obtained in step S1 is almost completely sublimated and released, causing graphite expansion.

[0080] Step S3: After the container is completely cooled, open the steel recovery bottle, scrape the anhydrous AlCl3 from the recovery bottle, collect, dry and seal. Open the flange hydrothermal reactor, scrape the expanded graphite from the inner tank, seal and collect. The final product is an expanded graphite-based composite material with extremely low residual intercalation content (content of 3.1%). Finally, 8g AlCl3 is recovered.

[0081] Example 4 This embodiment provides a method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, and the specific steps are as follows: Step S1: After drying 1 g of natural graphite with a particle size of 10 μm at 120° C. for 4 h, 4.5 g of anhydrous ferric chloride and 9 g of anhydrous aluminum chloride are quickly added and stirred at room temperature, and then vacuum dried at 80° C. for 5 h and transferred to a flange-type hydrothermal reactor. The flange-type hydrothermal reactor is sealed and placed in a heating furnace, heated to 650° C. and kept warm for 24 h to obtain a graphite intercalation compound, that is, an intermediate product of 1~2 order AlCl3-FeCl3-graphite intercalation compound is obtained.

[0082] Step S2: After the flanged hydrothermal reactor is completely cooled, the flange of the flanged hydrothermal reactor is loosened to facilitate gas overflow, and then placed in a sealable steel recovery bottle, and the recovery bottle is sealed. The whole is placed in a heating furnace and heated to 200°C (heating rate is 10°C / min) and kept warm for 1 hour. In this process, the intercalation substance AlCl3 of the graphite intercalation compound obtained in step S1 is almost completely sublimated and released, causing graphite expansion, while FeCl3 is preserved.

[0083] Step S3: After the container is completely cooled, open the steel recovery bottle, scrape the anhydrous AlCl3 from the recovery bottle, collect, dry and seal. Open the flange hydrothermal reactor, scrape the expanded graphite from the inner tank, seal and collect. The final product is a FeCl3-expanded graphite-based composite material. The obtained product is washed with deionized water, alcohol and acetone respectively and dried at 80°C for 12h. Finally, 7g AlCl3 is recovered.

[0084] Example 5 The difference from Example 3 is that the reaction temperature of step S1 is adjusted to 180°C, and the rest is the same as Example 3. Step S1 obtains an intermediate product of 3-5-order AlCl3-graphite intercalation compound; the final product of step S3 is an expanded graphite-based composite material with a residual intercalation content of 4.0%. Finally, 8g AlCl3 is recovered.

[0085] Example 6 The difference from Example 3 is that the reaction temperature of step S2 is adjusted to 180°C, and the rest is the same as Example 3. Step S1 obtains an intermediate product of 1~2-order AlCl3-graphite intercalation compound; the final product of step S3 is an expanded graphite-based composite material with a residual intercalation content of 5.0%. Finally, 8g of AlCl3 is recovered.

[0086] Example 7 The difference from Example 3 is that the reaction time of step S1 is adjusted to 24 hours, and the rest is the same as Example 3. Step S1 obtains an intermediate product of 1~2-order AlCl3-graphite intercalation compound; the final product of step S3 is an expanded graphite-based composite material with a residual intercalation content of 3.0%. Finally, 8g AlCl3 is recovered.

[0087] Example 8 The difference from Example 3 is that the reaction time of step S2 is adjusted to 0.5 h, and the rest is the same as Example 3. Step S1 obtains an intermediate product of 1~2-order AlCl3-graphite intercalation compound; the final product of step S3 is an expanded graphite-based composite material with a residual intercalation content of 3.5%. Finally, 8g AlCl3 is recovered.

[0088] Example 9 The difference from Example 3 is that the addition of 2g of chlorosuccinimide in step S1 is omitted, and the rest is the same as Example 3. Step S1 obtains an intermediate product of 3-5-order AlCl3-graphite intercalation compound; the final product of step S3 is an expanded graphite-based composite material with a residual intercalation content of 3.1%. Finally, 8g of AlCl3 is recovered.

[0089] Comparative Example 1 Untreated raw graphite PG.

[0090] Figure 2 These are the TG measurement results of the intercalant residues of Example 1, Example 3, Example 4 and Comparative Example 1.

[0091] Comparative Example 2 Step S1: add 15 ml of concentrated sulfuric acid and 8 ml of concentrated nitric acid to 8 ml of deionized water, stir in an ice bath; add 2 g of graphite, stir for 1 min; add ice cubes, add 6 g of potassium permanganate (can be added in batches depending on the viscosity of the reactants), a large amount of thick smoke is generated, stir for 90 min.

[0092] Step S2: Take 1L of water in a 3L beaker, place it in a fume hood, and slowly add concentrated sulfuric acid solution into the beaker along a glass rod; if the reactant has become a solid slurry, add a large amount of deionized water; if the reactant is in a solution, slowly transfer the reactant to a large amount of water, let it stand, pour out the upper solution, and centrifuge; wash with hydrogen peroxide to remove manganese oxide impurities, the judgment standard is that no bubbles emerge, and then wash to neutrality (3 times of water washing, 3 times of alcohol washing); after air drying for about 3 hours, transfer to a vacuum drying oven, and vacuum dry at 80°C for more than 24 hours to obtain expandable graphite.

[0093] Step S3: The large-diameter tubular furnace is heated to 1000° C. 50 mg of expandable graphite is taken and quickly placed in the constant temperature zone of the tubular furnace under protection. After 20 seconds, it is taken out and cooled to obtain the final product, conventional expanded graphite NEG.

[0094] The products obtained in Examples 1 to 4 and Comparative Example 2 and the original graphite PG were characterized by scanning electron microscopy (SEM) and X-ray diffractometer (XRD). Figure 3 and Figure 4 shown.

[0095] Figure 3The scanning electron microscope images of the products obtained in Comparative Examples 1-2 and Examples 1-4; Figure 4 The XRD patterns of the intermediate products obtained in step S1 of comparative examples 1-2 and embodiments 1-4 and the final products obtained in step S3 are shown.

[0096] Depend on Figure 3 and Figure 4 It can be seen that Example 1 obtains low intercalation residual expanded graphite (MoCl5-based), and the product shows a significant worm-like expansion effect (close to the traditional expanded graphite preparation process). This material only has a trace of MoCl5 remaining, which is suitable for the general use of expanded graphite. Example 2 obtains high intercalation residual expanded graphite (MoCl5-based), and the product only has micro-expansion phenomena such as particle enlargement and local edge opening. This material has a large amount of MoCl5 remaining, which can be used as a battery electrode material. Example 3 obtains low intercalation residual expanded graphite (AlCl3-based), and the product shows a significant worm-like expansion effect (close to the traditional expanded graphite preparation process). This material only has a trace of AlCl3 remaining, which is suitable for the general use of expanded graphite. Example 4 obtains FeCl3-expanded graphite composite material, and the product shows a significant worm-like expansion effect (close to the traditional expanded graphite preparation process). This material has a large amount of FeCl3 and a trace of AlCl3 remaining, which can be used as a battery electrode material.

[0097] Performance Test: The final products obtained in Comparative Example 1, Example 2 and Example 4 were used as electrode materials, and their electrochemical properties were evaluated using button half cells: First, prepare the battery. The specific steps are as follows: The final products obtained in Comparative Example 1, Example 2 and Example 4 were used as the positive electrode, the lithium sheet was used as the negative electrode, LB046 ether-based electrolyte was used, and CR2032 battery components were used to assemble the above components to obtain a half-cell.

[0098] Secondly, the electrochemical performance of the lithium-ion half-cell obtained above was tested using the Blue Electric system. The results are as follows Figure 5 shown.

[0099] Figure 5 The performance diagram of the battery prepared from the final products obtained in Example 2, Example 4 and Comparative Example 1. Figure 5 In the figure, the original graphite PG corresponds to proportion 1.

[0100] Depend on Figure 5 It can be seen that the battery assembled from the products of Example 2 and Example 4 has higher specific capacity and cycle stability, and still shows significant performance improvement at a large rate of 3C. The cost of industrialization is the main bottleneck restricting the application of such materials. The preparation method of the present invention is expected to overcome the cost bottleneck and create favorable conditions for the application of such materials.

[0101] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0102] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof, characterized in that: The steps include: The graphite substrate is mixed with the intercalation agent, and a molten salt intercalation reaction is carried out under closed conditions to obtain a graphite intercalation compound; Under semi-closed conditions, the graphite intercalation compound is heated for a second time to allow the intercalation agent to sublime and escape to obtain the expanded graphite-based composite material based on molten salt intercalation and controllable escape; The intercalant is a metal salt that can sublime under secondary temperature rising conditions.

2. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: The graphite substrate includes one or more of natural graphite, artificial graphite, microcrystalline graphite, expanded graphite and multilayer graphene; and / or the intercalant includes one or more of metal halides, metal sulfides and metal oxides.

3. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: The mass ratio of the graphite substrate to the intercalant is 1:0.1-14.

4. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: The temperature of the molten salt intercalation reaction is 100-800°C, the time is 0-24h, and is not 0.

5. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: The secondary heating temperature is 100-800°C, the heating rate is 10°C / min, the time is 0-1h, and is not 0.

6. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: The molten salt intercalation reaction also includes a step of controlling the order of the obtained graphite intercalation compound by using chlorine partial pressure; the reagent providing the chlorine partial pressure includes one or more of liquefied chlorine, chlorosuccinimide, phosphorus trichloride, phosphorus pentachloride, thionyl chloride and sulfonyl chloride.

7. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: After the second heating, the process also includes the steps of removing impurities and drying the product.

8. The method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to claim 1, characterized in that: The method also includes a step of modifying the expanded graphite based on molten salt intercalation and controllable release thereof.

9. The expanded graphite-based composite material based on molten salt intercalation and controllable release thereof prepared by the method for preparing an expanded graphite-based composite material based on molten salt intercalation and controllable release thereof according to any one of claims 1 to 8, characterized in that: The intercalation agent residual rate of the expanded graphite-based composite material based on molten salt intercalation and controllable release is 0-100%, and is not 0.

10. Use of the expanded graphite-based composite material based on molten salt intercalation and controllable release thereof as claimed in claim 9 in battery preparation.

Citation Information

Patent Citations

  • Microcrystalline graphite intercalation compound, expanded microcrystalline graphite and application

    CN119490184A